Age related changes in bleached enamel through scanning electron microscopy and atomic force microscopy - Mansoor, Afsheen; Moeen, Faisal; Mehmood, Mazhar; Mujtaba-ul-Hassan, Syed; Ubaidullah, Muhammad; Said, Farrukh (Pakistan Journal of Physiology, 2019)
ABSTRACT Objective:-To analyse the effect of bleaching on enamel morphology and roughness in different age groups. Study Design: a -In-vitro experimental study. Place and Duration of Studies:-Pakistan Institute of Engineering and Applied Sciences (PIEAS) from 1st October to 31st December 2018. Material and Methods:- 20 recently extracted upper central incisors of four different age groups,21-30 years (n=5), 31-40 years (n=5), 41-50 years (n=5) and 51-60 years (n=5) werewere taken and divided into two parts where one part of 5mm x 5mm x 2.5 mm of enamel specimenserved as a control group and the other counterpart as an experimental group. The control group wasobserved under AFM (Atomic Force Microscope) and then SEM (Scanning Electron Microscope). Enamel specimensof experimental groups were bleached with “Everbrite”, in-officetooth whitening system and were again studiedunder the AFM (Atomic Force Microscope) and SEM (Scanning Electron Microscope). Results:- There were significantly severe surface alterations and roughness observed in the young age group (21-30 years), moderate surface alterations and roughness found in the middle age group (31-40 years),whereas comparatively fewer surface alterations and unevenness was observed in the older age group, (41-50 years) and more elderly age group, (51-60 years) after the bleaching procedure. Conclusions:- The detrimental effects of hydrogen peroxide were significantly evident in teeth of all the age groups after the bleaching procedure as compared tothose belonging to the controlage groups under the AFM and SEM analysis. Keywords:- Extracted Teeth, Bleaching, SEM, AFM, Age.